Arab Spring di Maroko: Dari Demonstrasi Hingga Transisi Regulasi - Ahmad Zainal Mustofa (Jurnal ISIP: Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
This article describes the Arab Spring phenomenon that rocked the Middle East, especially Morocco. Arab Spring succeeded in bringing down the authoritarian leaders and dictators in power. This study uses decision-making theory to describe the problems that occur. Then the writer uses the descriptive-analytical method to fulfill the research sources to be studied. This research tries to answer the question how is the strategy of King Mohammed VI to avoid the storm of the Arab revolution after a series of protests that took place in his country? After conducting the research, we concluded that the strategy of King Mohammed VI in dealing with the wave of demonstrators in Morocco could be said to be different from the method used by other North African countries. King Mohammed VI changed his approach to problem-solving, not using violence but with a persuasive strategy. His efforts in stifling the turmoil of demonstrations in his country bore fruit. At least two factors contributed to his success in reducing protests in his country, namely the factors of openness and trust. This success made Morocco maintain its government without the fall of leadership. It is different from countries in the phenomenon of the Arab Spring.